Making myelin basic protein -from mRNA transport to localized translation - Müller, Christina; Bauer, Nina M.; Schäfer, Isabelle; White, Robin (Frontiers in Cellular Neuroscience, 2013)
In the central nervous system (CNS) of most vertebrates, oligodendrocytes enwrap neuronal axons with extensions of their plasma membrane to form the myelin sheath. Several proteins are characteristically found in myelin of which Myelin Basic Protein (MBP) is the second most abundant one after Proteolipid Protein (PLP). The lack of functional MBP in rodents results in a severe hypomyelinated phenotype in the CNS demonstrating its importance for myelin synthesis. Mbp mRNA is transported from the nucleus to the plasma membrane and is translated locally at the axon-glial contact site. Axonal properties such as diameter or electrical activity influence the degree of myelination. As oligodendrocytes can myelinate many axonal segments with varying properties, localized MBP translation represents an important part of a rapid and axon-tailored synthesis machinery. MBP’s ability to compact cellular membranes may be problematic for the integrity of intracellular membranous organelles and can also explain why MBP is transported in oligodendrocytes in the form of an mRNA rather than as a protein. Here we review the recent findings regarding intracellular transport and signalling mechanisms leading to localized translation of Mbp mRNA in oligodendrocytes. More detailed insights into the MBP synthesis pathway are important for a better understanding of the myelination process and may foster the development of remyelination therapies for demyelinating diseases.